Oral Janus kinase inhibitors in the treatment of atopic dermatitis: A systematic review and meta‐analysis - Kevin P. Lee; John Plante; Jeffrey E. Korte; Dirk M. Elston (Wiley, 2023)
Abstract Background Janus kinase (JAK) inhibitors are being evaluated as promising upcoming treatments for atopic dermatitis (AD). Objectives To systematically assess the efficacy of oral JAK inhibitors in patients with AD and provide comparisons among JAK inhibitors. Methods A systematic literature review of JAK inhibitors in the treatment of AD was conducted and reported based on Preferred Reporting Items for Systematic Reviews and Meta‐Analyses using PubMed, ClinicalTrials.gov, CENTRAL, MEDLINE/Ovid, Embase and sponsor websites from inception to 30 September 2021. References of relevant articles were reviewed by two authors. Only RCTs of JAK inhibitors for treating AD with more than one study were included. Data was extracted and the meta‐analysis was performed using the metan procedure in STATA version 12.1. Risk of bias was assessed with the Cochrane Risk of Bias Tool. The four outcomes analysed included Eczema Area Severity Index (EASI)‐75 response (≥75% improvement of EASI score from baseline), percent change in EASI score, percent of subjects achieving Investigator Global Assessment (IGA) of clear or almost clear (IGA 0/1), and ≥ 4‐point improvement in pruritus numerical rating scale (NRS). Results Fourteen randomized controlled trials (7051 subjects) assessing three different oral JAK inhibitors (abrocitinib, baricitinib and upadacitinib) in patients with moderate‐to‐severe AD were included in the meta‐analysis. Abrocitinib (100 and 200 mg), baricitinib (1, 2 and 4 mg) and upadacitinib (15 and 30 mg) were all found to be more efficacious compared to placebo in all four outcomes analysed. Upadacitinib 30 mg was more effective than all other dosages of JAK inhibitors in achieving EASI‐75, decrease in percent change of EASI, IGA 0/1 response rate, and ≥ 4‐point improvement in pruritus NRS. Conclusions JAK inhibitors were found to be an effective treatment for AD. Upadacitinib, at 30 mg, was found to be the most efficacious oral JAK inhibitor for AD. More clinical trial studies with comparisons among JAK inhibitors are needed to confirm these results as well as explore long‐term efficacy and safety of these molecules.